Magnetic excitations of perovskite rare-earth nickelates: RNiO3 - Buitrago Piñeros, Ivon Rocio (2015)
To gain insight into the ground state of perovskite nickelates RNiO3 (R: rare-earth), in particular charge disproportionation of the Ni ions and the magnetic configuration, we studied the magnetic excitations of the collinear, orthogonal and intermediate phases proposed for these materials. We used a localized spin model, including two kinds of Ni-spin magnitudes to describe an eventual charge disproportionation. For the magnetic couplings, we considered Heisenberg-like interactions up to next-nearest-neighbors, for the ferromagnetic and antiferromagnetic couplings present in the collinear phases. To describe the non-collinear phases, as proposed for other multiferroics, we considered Dzyaloshinskii–Moriya-type couplings to allow for the possibility of a relative angle θ, between nearest-neighbor spins in the two different magnetic sublattices. Using a simplified spin chain model for these compounds, we first analysed the stability of the collinear, orthogonal, and intermediate phases in the classical case. We then explored the quantum ground state indirectly, calculating the spin excitations obtained for each phase, using the Holstein–Primakoff transformation and the linear spin-wave approximation. For the collinear and orthogonal () phases we predict differences in the magnon spectra, concretely in the number of magnon branches or the magnitude of the magnon gap, which would allow to distinguish between these phases, and in particular probe the charge disproportionation, in future experiments such as inelastic neutron scattering or resonant inelastic X-ray scattering.